Perdagangan Satwa Liar Ditinjau Dari Convention On International Trade In Endangered Species Of Wild Fauna And Flaura - Nur Afya Ramadanti; Lucia Charlota Octovina Tahamata; Wilshen Leatemia (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Smuggling, trading, and theft of protected wild animals have increased quite high, such as orangutans, tigers, primates, and various other types of wildlife. It was recorded that since 2014 there were 14 cases until in 2016 the cases increased to 25 cases of illegal wildlife trade. This will have an impact on the lack of heritage biodiversity for mankind.Purposes of the Research: To find out about protection against wildlife trade according to the Convention On International Trade In Endangered Species Of Wild Fauna And FlauraMethods of the Research: The research used is normative juridical research. The research approach uses a legal approach, a conceptual approach and a case approach. Sources of research data are primary, secondary, tertiary data which is carried out by searching for library materials, namely studies related to international and national laws and regulations. The collection of legal materials is then analyzed qualitatively.Results of the Research: Wildlife protection according to the CITES convention is discussed in the classification of endangered species, non-threatened species, and registered species based on Appendix I, Appendix II and Appendix III. Appendix I lists and protects all wild flora and fauna species that are threatened with extinction so that they are prohibited from all forms of international trade. Meanwhile, Appendix II contains a list of Appendix II that are not threatened with extinction, but may be threatened with extinction if the trade in these species is not controlled. Then on the Appendix. III contains a list of flora and fauna species that have been protected by a certain country within the boundaries of their habitat area. The state must be responsible for the preservation of protected animals. Indonesian national laws regarding the protection of wild animals as well as endangered species should be maximized by conducting socialization to the public. The perpetrators of trade in protected wildlife must be given appropriate punishment and the need for a firm attitude from the government towards those who trade in animals in order to provide a deterrent effect for the perpetrators